Level attack of caterpillar on oil palm (Elaeis guineensis Jacq.) plantations in Dharmasraya District, West Sumatera Province, Indonesia - Zahlul Ikhsan; Dede Suhendra; Hidrayani Hidrayani; Sholih Kurniawati; Reza Tania (Universitas Trunojoyo Madura, 2023)
Caterpillars are insects that eat oil palm leaves. As a herbivore, its presence and feeding activity will be affected by the growth phase of the host plant. This study aims to determine the percentage and intensity of caterpillar attacks on oil palm (Elaeis guineensis Jacq.) which have not yet produced fruit in Dharmasraya Regency. The research was carried out in July-September 2022 and the location was determined using a purposive sampling method. The research was conducted in two immature oil palm plantations (Nagari Silago and Timpeh) and two mature areas (Nagari Sitiung and Muaro polite). Determination of sample plants was carried out diagonally and taken ± 10% of the total population of palms. The caterpillars found during the research in the oil palm plantations of Dharmasraya Regency consisted of 2 species, namely Setora nitens and Setothosea asigna. At the four study locations, the average percentage of infected plants, infected midribs, and attack intensity were 43.47; 40.71; and 19.86 %. Immature oil palm plants have a higher rate of fireworm attacks than mature ones.